Batik Anjani sebagai Agen Penggerak Ekonomi dan Pelestari Budaya Lokal di Desa Bumiaji - Rivo Abramovich Manurung; Arvi Ferdiansyah; Bagus Aditya Saputra; Dano Purba (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the role of Batik Anjani as an agent of local cultural preservation in Malang City, with a focus on the concept of agency within Anthony Giddens’ structuration theory. In this framework, an agent is understood as a social subject capable of acting reflectively and transforming their social environment. Batik Anjani, as a local batik industry actor, demonstrates initiative and awareness in preserving traditional values through production practices, motif selection, the use of natural materials, and community empowerment activities. Using a qualitative approach and case study method, this research analyzes how Batik Anjani actively makes decisions, formulates strategies, and constructs cultural meanings within the context of ever-changing socio-economic dynamics. The findings reveal that Batik Anjani does not merely fulfill an economic role but also acts as a cultural agent contributing to the sustainable preservation and reproduction of local cultural identity.